Recent Developments in Positron Emission Tomography Tracers for Proteinopathies Imaging in Dementia - Ni, Ruiqing; Nitsch, Roger M. (Frontiers in Aging Neuroscience, 2022)
Early detection and intervention for dementia represent tremendous unmet clinical needs and priorities in society. A shared feature of neurodegenerative diseases causing dementia is the abnormal accumulation and spreading of pathological protein aggregates, which affects the selective vulnerable circuit in a disease specific pattern. The advance in positron emission tomography (PET) biomarkers has accelerated the understanding of disease mechanism and development of therapeutics for Alzheimer’s disease and Parkinson’s disease. Clinical utility of amyloid- PET and clinical validity of tau PET as diagnostic biomarker for Alzheimer’s disease continuum have been demonstrated. The inclusion of biomarkers in the diagnostic criteria has introduced a paradigm shift, facilitated the early and differential disease diagnosis, and impacted on the clinical management. Application of disease modifying therapy likely requires screening of patients with molecular evidence of pathological accumulation and monitoring of treatment effect assisted with biomarkers. There is currently still a gap in specific 4-repeat tau imaging probes for 4-repeat tauopathies and -synuclein imaging probes for Parkinson’s disease and Dementia with Lewy body. In this review we focus on recent development in molecular imaging biomarkers for assisting the early diagnosis of proteinopathies in dementia (amyloid-, tau, and -synuclein) and discuss future perspectives.